Precision biotic as an effective replacement of hydrolyzed yeast and butyrate in antibiotic free diets of broiler chickens raised under field conditions - C. Bortoluzzi; M. Ghanbari; J.C. Gonzáles; J.O. Bohórquez; R. Paredes; Y. Mauri; C.A. Lozano-Poveda (Poultry Science)
A total of 1,436,000 Ross 380 AP broiler chicks were included in the experiment, which was conducted in two cycles with 20 houses per cycle and 35,900 birds per house. The objective was to evaluate, under field conditions, the impact of a precision biotic (PB) on the growth performance and cecal microbiome of broiler chickens, in comparison to enzymatically hydrolyzed yeast (EHY) and butyrate (BT) in an antibiotic-free diet. Each cycle consisted of six (6) houses under PB supplementation, and 14 houses under the regular dietary program used by the integration. Body weight (BW), feed intake (FI), and feed conversion ratio (FCR) were assessed at processing age, ranging from 39 to 45 d. Birds had ad libitum access to water and feed. On day 29, cecal content from 7 birds per house (42 birds per treatment) were collected for microbiome analysis by applying shotgun metagenomics approach. The performance data were analyzed by ANCOVA, house was considered as the experimental unit for growth performance (n = 20; P < 0.05), and the bird for microbiome analysis (n = 84; P < 0.05). Both treatment groups performed below the strain target in terms of BW, but better in terms of FCR. There were no significant differences (P > 0.05) between both groups on the growth performance, indicating that PB effectively replaced EHY and BT without compromising growth. However, significant functional changes were observed in the microbiome of birds fed PB, with enrichment in the pathways related to carbon and nitrogen metabolism. These changes were associated with an increased carbon metabolism index (P = 0.05), which can lead to higher endogenous short-chain fatty acids (SCFAs) production. Overall, by potentially increasing SCFA production by the intestinal microbiome, PB supported the growth performance of chickens similar to that achieved with EHY and BT.